Influence of controllable variables on the composting process, kinetic, and maturity of Stevia rebaudiana residues - J. J. Castro-Fernández; A. Serrato-González; M. Ruiz-Montoya; M. J. Díaz (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Stevia rebaudiana residues composting is studied and optimized using a central composite experimental design Methods The influence of controllable composting variables [moisture (40–70%), aeration (0.05–0.30 Lair min−1 kg−1), and time (0–50 days)] on the temperature history and the properties of the compost (pH, organic matter) produced to determine suitable composting conditions. Mass balance and emitted gases of all the composting reactors have been done. Results Compost with high degradation entails operating at 50 days of composting under high moisture content (70%) and aeration level with values close to 0.05 Lair min−1 kg−1. Moreover, the composting process kinetic for Stevia rebaudiana residues has been studied. The magnitude of the kinetic parameters on the studied conditions varies among 1/42 and 1/46 for 1/K 1 and 0.15 and 1.6 for K 2. Where 1/K 1 is a value that measures the affinity between microorganisms and substrate and K 2 depends on the composting variable optimization. Conclusions Both moisture and aeration affects positively and negatively the composting process. Moreover, low effect of aeration has been found. The values of 1/K 1 and K 2 obtained showed higher values (higher degradation kinetic) under 55% moisture content and 0.30 Lair min−1 kg−1.